Differential temporal patterns of insect populations visiting Cryptocoryne ciliate flowers - Kartini Saibeh; Mashhor Mansor (The Malaysian Society of Applied Biology, 1996)
Cryptocoryne ciliata is an amphibious aroid which is only found in mangrove areas in the Indo-Malayan region. Observation on insects visiting Cryptocoryne ciliata flowers were made during the flowering month of April in 1994 in the ten hectares oil palm plantation, Larut Matang (Perak). Fruit flies (Drosophilidae) and beetles (Nitidulidae) were found inside the kettle of the flower and could be considered as potential pollinators. However not all insects visiting the flowers were pollinators. Hoover flies (Syrphidae) were observed to destroy the flowers and the grasshoppers (Acrididae) apparently consumed the flowers and leaves. During a 24 hour period, a total of 313 insect individuals visited 120 flowers. The major pollinator insects were from the families Drosophilidae and Nitidulidae. They visited the flowers in a temporal clumped pattern with the Green Index values 0.029 and 0.130 respectively.